The application of fast scan cyclic voltammetry to the high speed channel electrode - Rees, N; Klymenko, O; Maisonhaute, E; Coles, B; Compton, R (2003)
The application of fast-scan cyclic voltammetry methods to the high-speed microband channel electrode (Rees et al. J. Phys. Chem. 99 (1995) 7096) is reported. Theory is presented to simulate cyclic voltammograms for a simple electron transfer under high convective flow rates within the high-speed channel. Experiments are reported for the oxidation of 9,10-diphenylanthracene (DPA) in acetonitrile solution containing 0.10 M tetrabutylammonium perchlorate (TBAP) for both 12.5 and 40 μm platinum microband electrodes using a range of scan rates from 50 to 3000 V s-1 and centre-line flow velocities from 12 to 25 m s-1. Analysis of the voltammograms yielded values for k0 and α for DPA which were measured to be 0.80±0.27 and 0.52±0.07 cm s-1, respectively. The range of applicability of this method was also investigated. Experiments are also presented using steady-state linear sweep voltammetry to obtain accurate measurements of the heterogeneous kinetic parameters for DPA at a platinum microband electrode. The measured value of k0 for DPA was found to be 0.94±0.16 cm s-1, with α = 0.53±0.02 and a formal oxidation potential of 1.40±0.01 V (vs. Ag).